The OECD's New Global Model - Hervé, Karine (OECD Economics Department Working Papers, 2010)
This paper provides a summary of the OECD's new global macroeconometric model, including an overview of model structure and a selection of simulations illustrating its main properties. Compared with its predecessors, the new model is more compact and regionally aggregated, but gives more weight to the focus of policy interests in global trade and financial linkages. The country model structures typically combine short-term Keynesian-type dynamics with a consistent long-run neo-classical supply-side. While retaining a conventional treatment of international trade and payments linkages, the model has a greater degree of stock-flow consistency, with explicit modelling of domestic and international assets, liabilities and associated income streams. Account is also taken of the influence of financial and housing market developments on asset valuation and domestic expenditures via house and equity prices, interest rates and exchange rates. As a result, the model gives more prominence to wealth and wealth effects in determining longer-term outcomes and the role of asset prices in the transmission of international shocks both to goods and financial markets